TREATMENT OF PREGNANT WOMEN INFECTED WITH SYPHILIS WITH INTRAVENOUS PENICILLIN G: PHARMACOKINETICAL AND CLINICAL STUDY - Mavrov, G.I.; Goubenko, T.V. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine")
Treatment of pregnant women infected with syphilis with intravenous infusions of penicillin G (2 million units every 12 hours) favors higher concentration of penicillin in blood serum (31 vs. 6-11 mkg/ml) and lower frequency and intensity of adverse effects (2.5 vs. 5.6%) in comparison with intramuscularly injections of benzyl penicillin (0.5–1.0 million units every 3 hours). Penicillin G favored a faster regress of clinical manifestations of syphilis (4-12 vs. 7-17 days) earlier obtaining negative results of serologic tests, more favorable outcomes of pregnancy if compared to group of patients who received benzyl penicillin. Thus, penicillin G is quite an effective medicine for treatment of pregnant women infected with syphilis.